Mediation And Arbitration in Asia-Pasifik - Syed Khalid Rashid, Syed Ahmad Idid (IIUM Press, 2009)
This is important book which presents the latest trends in mediation and arbitration in the asia pasific region. as settlement of civil and commercial disputes through litigation has become very costly and tedious,yhe modern worl is heavily leaning towards mediation and arbitration because of their comparative cost efficiency and simplicity